2015
DOI: 10.1016/j.susc.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surface intermediates during ethylidyne formation on Pt(111) by calculation of infrared intensities and deuterium isotope shifts

Abstract: a b s t r a c tThe conversion of ethylene to ethylidyne on Pt(111) is a well-studied model reaction related to conversion of hydrocarbons over noble metal catalysts. For this chemistry, a two step mechanism that proceeds via an ethylidene intermediate has been generally accepted since the mid-1990s. However, recent DFT calculations (J. Phys Chem. C 2010, 114, 12190) have suggested that this intermediate may, in fact, be short-lived and should not be observed. Experimental verification of this prediction, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
4
17
4
Order By: Relevance
“…In addition, DFT calculation showed that η-vinyl over the Pt(111), which preserves double bond nature, exhibited C=C vibration at 1547 cm -1 , much close to our experimental result, further supporting our proposal 45. Although the first step of propane dehydrogenation over metal oxides catalyst is commonly considered to be the dissociative adsorption of propane, forming metal alkyl and bridging hydroxyl, 28, 46-49 saturated alkyl (such as propyl) would not lead to the IR vibration as high as 1555 cm -1 50. Therefore, we propose that vanadium propyl would form at the first step of PDH, which instantly transforms to propenyl-vanadium due to instability, containing one C=C double bond and five H atoms.…”
supporting
confidence: 89%
“…In addition, DFT calculation showed that η-vinyl over the Pt(111), which preserves double bond nature, exhibited C=C vibration at 1547 cm -1 , much close to our experimental result, further supporting our proposal 45. Although the first step of propane dehydrogenation over metal oxides catalyst is commonly considered to be the dissociative adsorption of propane, forming metal alkyl and bridging hydroxyl, 28, 46-49 saturated alkyl (such as propyl) would not lead to the IR vibration as high as 1555 cm -1 50. Therefore, we propose that vanadium propyl would form at the first step of PDH, which instantly transforms to propenyl-vanadium due to instability, containing one C=C double bond and five H atoms.…”
supporting
confidence: 89%
“…The DFT‐determined lattice constant for Pt was found to be 3.98 Å, which agrees well with the experimental bulk lattice constant (3.92 Å); this lattice value is also consistent with other lattice constants reported in the literature for Pt . Four‐layer slab models were employed to model the Pt(111) surfaces in a super‐cell geometry with 1.2 nm vacuum spacing between them.…”
Section: Dft Calculationssupporting
confidence: 85%
“…Additionally, methane (CH 4 ), adsorbed methyl (CH 3 ), and carbonate (CO 3 2− ) groups were observed in small quantities on the catalyst surface. Gaseous CH 4 and adsorbed CH 3 were only found on the Pd and Ni/Al 2 O 3 catalysts at 600 °C, as indicated by the peaks at 3000 and 2890 cm −1  262728, respectively. This result is in agreement with the suppressed CO selectivity observed at 600 °C due to CH 4 formation.…”
Section: Resultsmentioning
confidence: 98%